Larvicide effects of Ricinus communis L. - Neves, Renato Teles; Rondon, Josimara Nolasco; Silva, Lenice Inácio Mota da; Peruca, Ricardo Dias; Ítavo, Luiz Carlos Vinhas; Carvalho, Cristiano Marcelo Espinola; Souza, Antonio Pancracio de; Fabri, Joao Roberto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Effective larvicides in low concentrations, and is easily obtained in the region, are intensely sought by public health agencies. Therefore, the aim of this study was to evaluate the potential larvicide leaf extract and oil of the fruit of Ricinus communis on the larvae of Aedes aegypti. The results showed that seed and leaf extracts promoted total mortality of the larvae, and this effect is independent of concentration. Therefore, indicates the use of R. communis in endemic regions to control larvae.